If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(4x-1)-3x+5=-26
We move all terms to the left:
-2(4x-1)-3x+5-(-26)=0
We add all the numbers together, and all the variables
-3x-2(4x-1)+31=0
We multiply parentheses
-3x-8x+2+31=0
We add all the numbers together, and all the variables
-11x+33=0
We move all terms containing x to the left, all other terms to the right
-11x=-33
x=-33/-11
x=+3
| -5(x-3)+7x=39 | | 2v-25=57 | | 14y-9=17y+12 | | 9(z+1)=99 | | w/(-8)=15 | | 0.8x=112 | | 50220=1.08x | | 5x=5×+12 | | C(20)=0.06x+15.75 | | 2x^2+7=105 | | -4(2x+5)+5x-1=-48 | | 320=200+.15x | | -17x-16=67 | | k/2+8=11 | | 2w+3(w)=77 | | 16y+38=166 | | 66=6x+24 | | 4(k-8)+1=33 | | 3x+0.9=15.9 | | 2(3.14)1.5=c | | 2x-28=2 | | 120=−6d+6 | | 7(3-2)+z=5-2z | | 47=3d+8 | | h+12.6=−12.6 | | w+11/7=6 | | 7/4r+14=-14 | | −6p+48=12 | | 3(-4-1)-2x+4=43 | | 6(31)-7+8y+17=180 | | 16=10+3r | | (3.5x-1.5)=(5x-3) |